Implementation of Gender Equality and Social Inclusion (GESI) in Islamic University in Indonesia - Nikmatullah Nikmatullah; Guruh Sugiharto; Riska Mutiah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article aims to determine the policy and practice of gender equality and social inclusion (GESI) in Islamic universities in Indonesia, with a particular focus on the State Islamic University (UIN) Mataram. This qualitative research was carried out for 5 months in 2023, using indicators of gender-responsive higher education through observation, interviews, and documentation. Meanwhile, the analysis is carried out through three stages, namely restatement, description, and interpretation. Studies show that UIN Mataram has moved towards gender-responsive higher education. Some gender-responsive policies have been implemented to create an inclusive campus. The application of GESI can be observed through four dimensions: institutional, three pillars of higher education, institutional governance, and culture of non-violence. Although the university leadership is dominated by men, gender-responsive men can serve as role models to encourage inclusive cultural transformation. UIN Mataram has had a Center for Gender and Child Studies since 2002, which conducts gender programs, activities, and advocacy; gender textbooks to guide teaching and learning in the classroom; the involvement of female lecturers in research; the provision of support for women-friendly villages; the availability of facilities to address practical gender needs; the establishment of UIN Care, which focuses on preventing and responding to sexual violence; and the Center for Literacy and Social Disability Studies and Services (PUSKA LDS), which fosters social inclusion. Factors such as patriarchal culture, religious understanding, and leadership commitment have an impact on the implementation of GESI in the Islamic university.